2011
DOI: 10.3390/ijms12084975
|View full text |Cite
|
Sign up to set email alerts
|

Transient Co-Expression of Post-Transcriptional Gene Silencing Suppressors for Increased in Planta Expression of a Recombinant Anthrax Receptor Fusion Protein

Abstract: Potential epidemics of infectious diseases and the constant threat of bioterrorism demand rapid, scalable, and cost-efficient manufacturing of therapeutic proteins. Molecular farming of tobacco plants provides an alternative for the recombinant production of therapeutics. We have developed a transient production platform that uses Agrobacterium infiltration of Nicotiana benthamiana plants to express a novel anthrax receptor decoy protein (immunoadhesin), CMG2-Fc. This chimeric fusion protein, designed to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…The expression of hGAD65mut in transgenic tobacco plants has been previously reported 12 , showing that recombinant protein levels varied significantly among independently transformed lines. The best-performing hGAD65mut T1 transgenic plant was self-crossed and the derived plants (T2) were analyzed to select again the best performing one.…”
Section: Representative Resultsmentioning
confidence: 88%
“…The expression of hGAD65mut in transgenic tobacco plants has been previously reported 12 , showing that recombinant protein levels varied significantly among independently transformed lines. The best-performing hGAD65mut T1 transgenic plant was self-crossed and the derived plants (T2) were analyzed to select again the best performing one.…”
Section: Representative Resultsmentioning
confidence: 88%
“…It has been also mentioned that PTGS plays a key role in shortening the transient expression period (Voinnet et al 2003). Meanwhile, according to the studies of Arzola et al (2011) andVoinnet et al (2003), the coinfection of infiltrated leaves with a viral-silencing suppressor may improve the transgene expression level. It has been also reported that the use of 2b derived from CMV could enhance expression levels of different proteins in N. benthamiana up to 5.5-fold (Moon et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, two signal peptides, Zera ® (Mainieri et al 2014) andExtensin (De Loose et al 1991), were utilized to examine the potential roles of each on the accumulation of the recombinant IpaD protein in the plants under study. Meanwhile, an approach based on suppression of posttranscriptional gene silencing (PTGS) was employed using Cucumber mosaic virus (CMV) 2b protein (Goto et al 2007;Arzola et al 2011) to determine its effect on the production quantity of the current recombinant IpaD protein.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, the DNA plasmid constructs engineered by researchers to be transferred from bacteria into plants have historically incorporated or built upon genetic elements of tobacco mosaic virus (TMV) or other plant viruses that replicate in tobacco leaves, therefore further justifying the use of tobacco as a plant host for expression of these target biotherapeutics. [Mallajosyula, 2014: 24378714], [Kalthoff, 2010: 20810729], [Kanagarajan, 2012: 22442675] Ebola virus [12][13][14][15] [ Phoolcharoen, 2011: 21281425], [Phoolcharoen, 2011: 22143779], [Huang, 2010, 20047189], [Castilho, 2011: 22039433] Dengue [16][17][18][19][20] [ Kim, 2015: 25728317], [Conconi-Linares, 2013: 23499580], [Saejung, 2007: 17659815], [Martinez, 2010: 20213522], [Martinez, 2012: 22480936] Norovirus [21][22][23][24][25] [ Mathew, 2014: 24949472], [Santi, 2008: 18325641], [Lai, 2012: 22134876 [Farrance, 2011: 21715576], [Feller, 2013: 24278216], [Kapelski, 2015: 25651860], [Voepel, 2014: 25200253], [Clemente, 2012: 22911156], [Beiss, 2015: 25615702], West Nile Virus [49][50][51] [ Chen, 2015: 25676782], [Lai, 2014: 24975464], 24675995] Bacillus anthracis (anthrax) [52][53][54][55][...…”
Section: Open Accessmentioning
confidence: 99%